THE EFFECT OF SALES, PRODUCTION COSTS, TOTAL DEBT AND WORKING CAPITAL ON NET PROFIT OF MANUFACTURING COMPANIES PHARMACEUTICAL SUB SECTOR - Indrayani, Indrayani; Gani, Akbar; Mursidah , Mursidah; Yunina, Yunina (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2022)
This study examined the effect of sales, production costs, total debt, and working capital on the net profit of pharmaceutical sub-sector manufacturing companies listed on the Indonesia Stock Exchange in 2017-2020. The sample selection technique used was purposive sampling and obtained 10 pharmaceutical sub-sector manufacturing companies listed on the Stock Exchange. This study used balanced panel data with 40 observations and estimates (fixed-effect model). The results indicated that sales and working capital did not influence net income. Meanwhile, production costs positively and significantly influenced net income. The total debt negatively and significantly influenced net income in the pharmaceutical sub-sector manufacturing companies listed on the IDX in 2017-2020.